KINETICS OF SOLVENT EXTRACTION OF ZIRCONIUM (IV) FROM CHLORIDE MEDIUM BY D2EPHA IN KEROSENE USING THE LEWIS CELL TECHNIQUE: A COMPARISON WITH SINGLE DROP TECHNIQUE (Biological Sciences - PJSIR, 2004)
The kinetics of the title system has been investigated by the Lewis cell technique for 1-day ageing of the aqueous phase and compared with those obtained from the single drop technique. The mass transfer flux equations for Zr(IV) have been derived for three aqueous acidities of 0.10, 1 and 5 mol dm-3  HCl, respectively, as: J (kmol m-2s-1  = 10-5.53±0.04 (1+0.00038[Zr(IV)]-1)-1 [H+][H A ] (1+0.70[Cl-]), J (kmol m-2s-1) = 10-5.80±0.02  1+0.004 [Zr(IV)]-1)-1 [H A ] [Cl-] and 2    2  (o)                                                                                                                                                            2     2  (o)J (kmol m-2 s-1) = 10-6.58± 0.03 (1+0.0038 [Zr(IV)]-1)-1[H]+[H A ]   [Cl-]. The values of E  (kJ mol-1) in kinetic and diffusion2    2  (o)                                                 aregimes are 92 & 14.7 and 84 & 15 for 1 and 5 mol dm-3 HCl systems, respectively. For 0.10 mol dm-3 HCl system, Ea value cannot be measured for kinetic regime but its value is 15 kJ mol-1 in diffusion regime. At intermediate controlled regime (Zr(IV) » 3 mmol dm-3), Ea value varies from 11, 12 and 12 kJ mol-1 to 42, 105 and 108 kJ mol-1 respectively, for 0.10, 1 and 5 mol dm-3 HCl systems on varying the temperature from 318 K to 288 K. .On the basis of these data, the mechanisms of extraction in different conditions have been suggested.